Wacana Kritis Perbandingan Tiga Kandidat dalam Debat Pemilihan Gubernur Jawa Timur 2024: Analisis Korpus - Hadi Asrori; Almira Fidela Artha; Dika Prestiawan (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study analyzes the use of verbs in the 2024 East Java Gubernatorial Debate from the perspective of Norman Fairclough's discourse analysis, which includes text, discourse practice, and social practice. The main objective of this research is to identify the verbs most frequently used by each pair of candidates (paslon) using the AntConc software. The method employed is qualitative descriptive, where data is collected from debate transcripts converted into .txt format and analyzed to identify the dominant verbs. The results show thirteen commonly used verbs, such as “obtain”, “ensure”, “present”, and “give”. The Luluk-Lukman pair frequently used the verbs “ensure”, “obtain”, and “give” to emphasize welfare; Khofifah-Emil used “present”, “build”, and “give” to highlight achievements; while Tri Rismaharini-Gus Hans used “give”, “obtain”, and “make” to focus on education and social togetherness. This research highlights the importance of critical discourse analysis in understanding political communication strategies and can be further developed to analyze political debates at other local levels.